Convergence and the effects of spatial interaction - Annekatrin Niebuhr (Hamburg Institute of International Economics (HWWA), 2000)
Since the beginning of the 1990s, the issue of income convergence has received considerable attention in economic research. Although a vast number of empirical studies has emerged, evidence on the role of spatial interaction is still rather scarce. The present paper is an attempt to provide additional information on the spatial aspect of convergence. Spatial econometric methods are used to investigate regional convergence in West Germany. The results indicate that spatial interaction is an important element of regional growth. However, considering spatial effects does not alter the general conclusion that regional income growth is characterised by a process of convergence.
Keywords: O18; C52; C21; R11; 330; Regional convergence; Spatial interaction; Spatial econometrics; Regionale Entwicklung; Regionales Wachstum; Entwicklungskonvergenz; Räumliche Interaktion; Spillover-Effekt; Schätzung; Deutschland; Alte Bundesländer